An adaptive 5G multiservice and multitenant radio access network architecture. Issue 9 (September 2016) - Droste, Heinz; Rost, Peter; Doll, Mark; Berberana, Ignacio; Mannweiler, Christian; Breitbach, Markus; Banchs, Albert; Puente, Miguel A.
Abstract: This article provides an overview on objectives and first results of the Horizon 2020 project 5G NOvel Radio Multiservice adaptive network Architecture (5GNORMA). With 5G NORMA, leading players in the mobile ecosystem aim to underpin Europe's leadership position in 5G. The key objective of 5G NORMA is to develop a conceptually novel, adaptive and future‐proof 5G mobile network architecture. This architecture will allow for adapting the network to a wide range of service specific requirements, resulting in novel service‐aware and context‐aware end‐to‐end function chaining. The technical approach is based on an innovative concept of adaptive (de)composition and allocation of mobile network functions based on end‐user requirements and infrastructure capabilities. At the same time, cost savings and faster time to market are to be expected by joint deployment of logically separated multiservice and multitenant networks on common hardware and other physical resources making use of traffic multiplexing gains. In this context architectural enablers such as network function virtualization and software‐defined mobile networking will play a key role for introducing the needed flexible resource assignment to logical networks and specific virtual network functions. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This article provides an overview on objectives and first results of the Horizon 2020 project 5G Novel Radio Multiservice adaptive network Architecture. Besides the fundamental components of the of the Novel Radio Multiservice adaptive network Architecture, novel views on a radio network architecture are motivated, and as a result, a first reference architecture is presented.